Development And Alpha Testing Of Ezhifz Application: Al-quran Memorization Tool - Nor Musliza Mustafa; Mokmin Basri; Sedek Ariffin; Zulkifly Mohd Zaki; Khairul Anuar Mohamad (Hindawi, 2024)
Indexed by WOS/SCOPUS/ERA